Water Droplet With Carbon Particles Moving Through High-Temperature Gases; Journal of Heat Transfer; Vol. 138, iss. 1 - Volkov R. S. Roman Sergeevich; Piskunov M. V. Maksim Vladimirovich; Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich (2016, 2016)
Title screen